Analysis Of The Traits Contributing Towards Yield In Okra (Abelmoschusesculentus (L.) Moench ) (International Journal of Food and Nutritional Sciences, 2021)
The present investigation was carried out on 32 genotypes of okra at Agricultural Research Farm of Rama University, Kanpur during year 2019-20 for yield and its attributing traits. Various morphological parameters viz., days to 50% flowering, plant height (cm), number of branches/plant, length of fruit per plant(cm), diameter of pod (cm), number of seeds per pod, number of fruits per plant and edible fruit yield per plant (g) were recorded. At genotypic and phenotypic levels, days to 50 % flowering exhibited significant positive correlation with number of branches per plant. Plant height revealed significant positive correlation with number of fruits per plant followed by fruit diameter. Number of fruits per plant showed significant positive correlation with fruit length. At both genotypic and phenotypic level, path coefficient analysis revealed maximum direct effect in case of fruit diameter. However, fruit diameter showed significant positive highest indirect effect on yield. The traits which were correlated positively with yield can be used as selection criteria in crop improvement program.